Piero Sanpaolesi e il Museo Nazionale dell’Iran antico. Un atteggiamento critico per un’architettura del Novecento / Piero Sanpaolesi and the National Museum of Ancient Iran: A Critical Approach to Twentieth-Century Architecture - Pisani, Francesco (Restauro Archeologico, 2025)
The article analyses Piero Sanpaolesi’s intervention on André Godard’s National Museum of Iran (Tehran, 1936) as an exemplary case of his critical approach to modern architecture. Sanpaolesi’s method, based on analytical observation and respect for material authenticity, is applied here to a twentieth-century building within a non-European context. Through archival sources and comparative analysis, the paper highlights how his attitude anticipates contemporary debates on the preservation of modern heritage and demonstrates the international dimension of Italian restoration theory in the 1960s-1970s.